Trade Integration and Growth : Evidence from Sub-Saharan Africa - Calderon, Cesar (World Bank, Washington, DC, 2019)
This paper examines the growth effects of different dimensions of international trade integration -- notably, volume, diversification, and natural resource dependence -- in Sub-Saharan Africa. First, the paper documents the recent trends in these foreign trade dimensions for the region and the traditional sources of growth. Second, it empirically estimates the impact of trade integration on growth per worker and the sources of growth; that is, growth of capital per worker and total factor productivity growth. To accomplish this task, the analysis uses a sample of non-overlapping five-year period observations for 173 countries from 1975 to 2014. The econometric evidence shows that increased trade openness, greater export production diversification, and reduced export dependence from natural resources will have a positive causal impact on economic growth. These effects will be mainly transmitted through faster capital accumulation or enhanced total factor productivity growth. Finally, the paper finds that, despite the progress exhibited in trade openness and diversification over the past decade, there are still potential benefits that can be accrued if countries were to deepen their integration to world trade.